THE EFFECTIVENESS OF VISUAL AIDS IN EFL - Ibragimova , Shakhnoza (INTERNATIONAL CONFERENCES, 2023)
This paper focuses on using visual tools in teaching English as a foreign language classroom with an emphasis on the role of visual tools in facilitating the teaching and learning of language content. This paper will provide learners’ attitude towards using visual aids in multimedia classrooms in their learning process, as well as effectiveness of visual aids in learning and teaching English as a foreign language.